Activity of the inflammatory process depending on sputum markers in children with different onset of bronchial asthma - Білоус, Володимир Володимирович (Pediatria i Medycyna Rodzinna, 2022)
Aim of the study: To analyse the activity of the inflammatory process in the airways in children with bronchial asthma depending on the onset of the disease. Materials and methods: In compliance with the principles of bioethics, a comprehensive retrospective examination of 319 children suffering from bronchial asthma was performed. In 257 children (clinical group I), bronchial asthma developed on the background of chronic obstructive bronchitis. The second (II) clinical group included 43 children, in whom asthma occurred after community-acquired pneumonia. The third (III) clinical group consisted of 19 children in whom asthma was first verified after inpatient treatment for asthmatic status. Results: Based on the severity of bronchial asthma, it was found that the representatives of the clinical group III, compared with other patients, significantly more often had a severe course of the disease. For patients of the clinical group I, the onset was characterised by increased eosinophils and decreased neutrophil counts in sputum, for group II patients – increased eosinophils and epitheliocytes, but a decrease in lymphocytes, and in children of the clinical group III – low eosinophils in the sputum with a simultaneous increase in neutrophils. In particular, a statistically significant increase in the level of vascular endothelial growth factor, and a decrease in the content of cationic proteins, matrix metalloproteinase-9, and interleukins 6 and 13, in sputum indicates the predominance of neoangiogenesis in children of the clinical group III. Instead, in the clinical group II the remodelling processes were mainly caused by the inflammatory process with the release of intracellular eosinophilic cationic proteins. Conclusion: These data indicate the discrete nature of the type and severity of the inflammatory process of the respiratory tract over the dynamic follow-up period in children classified in different clinical comparison groups, which suggests the presence of certain phenotypic differences due to alternative onsets of the disease, which were determined by different triggers. Such deviations in the inflammatory process indicate that patients with asthma require a personalised approach to ensure differentiated diagnostic monitoring and targeted anti-inflammatory treatment, taking into account the peculiarities of the onset of the disease.
Keywords: children; bronchial asthma; onset of the disease; sputum markers